Mola tecta Nyegaard, Sawai, Gemmell, Gillum, Loneragan, Yamanoue, & Stewart 2018 - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Mola tecta Nyegaard, Sawai, Gemmell, Gillum, Loneragan, Yamanoue, & Stewart, 2018. Hoodwinker Ocean Sunfish. To at least 242 cm (95.3 in) TL (Nyegaard et al. 2018). Southern Hemisphere from Chile to Australia to South Africa, and one possible record from the North Sea (Nyegaard et al. 2018); at least as far north as Kodiak Island, Alaska (Marianne Nyegaard, pers. comm.) to Coal Oil Point, Santa Barbara County, southern California (M.L., pers. obs.). Depth range unknown, but may resemble that of Mola mola (Linnaeus, 1758) (Nyegaard et al. 2018). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 227, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008